An empirical analysis of long-term Brazilian interest rates - Tanweer Akram; Syed Helal Uddin (Levy Economics Institute of Bard College, 2020)
This paper empirically models the dynamics of Brazilian government bond (BGB) yields based on monthly macroeconomic data in the context of the evolution of Brazil's key macroeconomic variables. The results show that the current short-term interest rate has a decisive influence on BGBs' long-term interest rates after controlling for various key macroeconomic variables, such as inflation and industrial production or economic activity. These findings support John Maynard Keynes's claim that the central bank's actions influence the long-term interest rate on government bonds mainly through the short-term interest rate. These findings have important policy implications for Brazil. This paper relates the findings of the estimated models to ongoing debates in fiscal and monetary policies.
Keywords: E43; E50; E58; E60; G10; G12; 330; Brazilian Government Bonds; Long-Term Interest Rate; Bond Yields; Monetary Policy; Short-Term Interest Rate; Banco Central do Brasil (BCB)